Driving mechanisms of Holocene coastal evolution in the Bonifacio Strait (Western Mediterranean) - Vacchi, Matteo; Ghilardi, Matthieu; Stocchi, Paolo; Furlani, Stefano; Rossi, Veronica; Buosi, Carla; Rovere, Alessio; De Muro, Sandro (Marine Geology, 2020)
We produced a new suite of sea-level data which allowed assessing the Holocene evolution of the Bonifacio Strait, a key coastal sector of the Mediterranean Sea which experienced significant morphological changes since the Last Glacial Maximum. Squeezed between Corsica and Sardinia islands, this strait connects the two major basins of the western Mediterranean. Due to its peculiar geographic and morphological setting, the Bonifacio Strait is affected by extreme meteomarine conditions characterized by severe winds, waves, and currents. The millennial sea-level changes were reconstructed through multiproxy investigations made of sediment coring and underwater beachrock sampling carried out on both sides of the strait. These data provided fresh insights into the timing of the progressive opening of the Bonifacio Strait which followed the Last Glacial Maximum when Corsica and Sardinia were connected forming the largest Mediterranean island. Major palaeogeographic changes occurred before ~7 ka BP. Since that period, the significant decrease of the northern ice-sheet melting triggered a significant sea-level stabilization which induced only minor modifications in the palaeogeography of the strait. In the late Holocene, the isostatic-related subsidence became the dominant factor controlling the sea-level changes which rose with rates ≤0.35 mm a−1 in the last four millennia. Our data have also an important archaeological implication because they indicate that the Bonifacio Strait has not represented a significant geographical barrier along the early Neolithic migration path which connected mainland Italy to northern Corsica and finally to Sardinia. This further confirms the ability of early Neolithic communities to navigate not also across large sea stretches but also maritime areas characterized by extremely complex meteomarine conditions.